New Directions in the Study and Treatment of Metastatic Cancer - Yoo, Byunghee; Fuchs, Bryan C.; Medarova, Zdravka (Frontiers in Oncology, 2018)
Traditional cancer therapy has relied on a strictly cytotoxic approach that views non-metastatic and metastatic tumor cells as identical in terms of molecular biology and sensitivity to therapeutic intervention. Mounting evidence suggests that, in fact, non-metastatic and metastatic tumor cells differ in key characteristics that could explain the capacity of the metastatic cells to not only escape the primary organ but also to survive while in the circulation and to colonize a distant organ. Here, we lay out a framework for a new multi-pronged therapeutic approach. This approach involves modifying the local microenvironment of the primary tumor to inhibit the formation and release of metastatic cells; normalizing the microenvironment of the metastatic organ to limit the capacity of metastatic tumor cells to invade and colonize the organ; remediating the immune response to tumor neoantigens; and targeting metastatic tumor cells on a systemic level by restoring critical and unique aspects of the cell’s phenotype, such as anchorage dependence. Given the limited progress against metastatic cancer using traditional therapeutic strategies, the outlined paradigm could provide a more rational alternative to patients with metastatic cancer.